Investigations of In vitro Digestibility of Proteins Bound to Food Colors - Ghufran Saeed, Syed Muhammad; Sayeed, Syed Asad; Ashraf, Seema; Nassimunnisa, Nassimunnisa; Batool, Fizza; Ali, Rashida; Naz, Shahina; Siddiqi, Rahmanullah (Journal of Pharmacy and Nutrition Sciences, 2022)
Colorants either synthetic or natural are commonly added to a variety of food systems to make them attractive and acceptable for the consumers. Our previous publications on Carmoisine, Allura Red, Sunset yellow and the present study showed that food colorants such as Erythrosine, Amaranth, Tartrazine, Quinoline yellow, Brilliant Blue bind with the proteins in variety of the food environments and the protein color complexes are digested by the proteolytic enzyme. The present study elaborates the active sites of the proteins involved in binding with various functional groups of food colors and on these sites modifies the tryptic digestibility of the different proteins. Colors show strong binding capacity with proteins which may block the active site for hydrolysis by the enzyme. The effect of the tryptic digestibility on color complexes of the protein such as the BSA a high molecular weight and nisin the low moleculer weight proteins are explored. The result shows the different color binding with protein have not similar effect on digestibility but in all cases digestibility decreases significantly as compared with blank.